Treatment-Associated Acute Lymphoblastic Leukemia Following Autologous Hematopoietic Stem Cell Transplant and Lenalidomide Maintenance in Patients With Multiple Myeloma. (October 2022) - Crosby, James; Erzuah, Tosha; Haider, Mahvish; Smith, Forrest; Ganti, Shyam; Monohan, Gregory; Elsouiedi, Raymond
Secondary malignancies including leukemia are an increasing concern in patients with prior primary malignancies treated with alkylating agents or topoisomerase II inhibitors. These can also be referred to as therapy-related leukemia. Therapy-related leukemia most commonly results in myelodysplastic syndrome or acute myeloid leukemia. The alkylating agent can cause chromosomal aberrations typically manifest as deletions in chromosome 11 or loss of part of complete loss of chromosomes 5 and 7. Conversely, acute lymphoblastic leukemia (ALL) has been described following maintenance therapy with immunomodulatory (IMiD) drugs pomalidomide, thalidomide, and lenalidomide. We present a case of a 71-year-old man with a history of multiple myeloma (MM) maintained on lenalidomide after stem cell transplant who presented with treatment-associated ALL. At time of leukemic presentation, chromosomal analysis showed a near-triploid clone consistent with masked double low hyplodiploidy which is associated with a poor prognosis. The patient had a deletion of the long arm of chromosome 5 which has been described in prior case reports with ALL secondary to lenalidomide therapy. There are explicit mechanisms in the literature, which have been attributed to development of ALL after exposure to thalidomide or lenalidomide. At time of submission, there are 20 cases described in the literature linking ALL to IMiD drugs. We describe a case and review the mechanisms of lenalidomide-associated ALL.